Strategi Komunikasi Pemasaran Produk Unit Link PT Asuransi Jiwa Manulife untuk Menarik Minat Calon Nasabah - Nabilah Salsabilah ; Nuri Aslami (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2022)
This journal contains the communication strategy of Unit Link Product Marketing of PT. Manulife Life Insurance to Attract Prospective Customers which is focused on the steps in describing the strategy undertaken by PT. Manulife in increasing the number of its customers. The research method is descriptive qualitative method with data analysis techniques Interactive Model Matthew B. Miles and A. Michael Huberman. The results of the study obtained an illustration that in the communication strategy of Unit Link Product Marketing of PT. Manulife Life Insurance to Attract Prospective Customers by prioritizing two-way communication to customers to sell their products in order to give influence, confidence, and actions taken as encouragement can be seen by using steps in developing effective marketing communications to achieve goals that have been established and can be implemented properly. Keywords: Communication, Communication Strategy, Marketing, Manulife Life Insurance, Interests.